rearrange these to make x the subject
V W
3X = Y
VX-W=2
6X(SQUARED) + VX = Y
1) Have you written: $\displaystyle \frac{VW}{3X}=Y$?
If so, multiply both sides of the equation by 3X.
$\displaystyle VW=3XY$
Divide both sides by 3Y.
$\displaystyle \frac{VW}{3Y}=X$
$\displaystyle \boxed{X=\frac{VW}{3Y}}$
2)
$\displaystyle VX-W=2$
Add W to both sides.
$\displaystyle VX-W+W=2+W$
Divide both sides by V.
$\displaystyle \boxed{X=\frac{2+W}{V}}$
3)
$\displaystyle 6X^2+VX=Y$
Somehow, after looking at the first two, this one seems a bit out of place. I won't explain each step. I'll just perform them.
$\displaystyle 6\left(X^2+\frac{V}{6}X+\frac{V^2}{144}\right)=Y+6 \left(\frac{V^2}{144}\right)$
$\displaystyle 6\left(X+\frac{V}{12}\right)^2=Y+\frac{V^2}{24}$
$\displaystyle 6\left(X+\frac{V}{12}\right)^2=\frac{24Y+V^2}{24}$
$\displaystyle \left(X+\frac{V}{12}\right)^2=\frac{24Y+V^2}{144}$
$\displaystyle X+\frac{V}{12}=\frac{\pm \sqrt{24Y+V^2}}{12}$
$\displaystyle \boxed{X=\frac{\pm \sqrt{24Y+V^2}-V}{12}}$
I don't know how clean that last one is. Maybe some others will critique it.